Wayang Kulit sebagai Instrumen Edukasi: Re-Interpretasi Wayang Kulit di Museum Volkenkunde Leiden and Museum Wayang Kekayon Yogyakarta - Permata, Kezia (Javanese Language, Literature, and Culture Study Program, Universitas Gadjah Mada, 2023)
This research aims to analyze the influence of the relocation and timing on the educational value embedded in wayang kulit. Using the theory of